Maternal Anxiety Symptoms and Mother-toddler Diet Quality Among WIC Participants (OR03-08-19) - Trude, Angela (Curr Dev Nutr, 2019)
OBJECTIVES: To evaluate the longitudinal association between maternal anxiety and diet quality among low-income mothers and toddlers. METHODS: Longitudinal study of data collected from 267 mother-toddler dyads in an obesity prevention trial recruited from Maryland Special Supplemental Nutrition Program for Women, Infants and Children (WIC) and pediatric clinics between 2007 and 2010. Dyads were assessed at 3-time points (baseline, 6-, 12-mo follow-up). Healthy Eating Index (HEI-2015, dependent variable) estimated maternal and toddler diet quality obtained from a 24-h dietary recall (one day). Anxiety (time-variant independent variable) was assessed via State-Trait Anxiety Inventory. Mixed models assessed the longitudinal associations between maternal anxiety and maternal and toddler diet quality, separately, controlling for sociodemographic, maternal body mass index (BMI), and household food security. No significant effect by intervention group was found, thus intervention was treated as a covariate. An interaction term assessed the variation between anxiety and diet quality by time. RESULTS: Mothers mean age was 27.1 (SD ± 6.2) years and anxiety 1.7 (± 0.6). Toddlers were on average 20.2 months old (± 5.6). Mean HEI at baseline was 47.9 (± 12.1) and 54.1 (± 10.5) for mothers and toddlers, respectively. Maternal anxiety was negatively related to toddler HEI score (β = −2.7, 95% CI: −4.9; −0.5) with no significant variation over time. There was a significant negative variation between maternal anxiety and maternal diet at baseline (β = −3.9, 95% CI: −6.2; −1.6) and 6-mo (β = −3.2, 95% CI: −5.9; −0.5), but not at 12-mo (β = −0.4, 95% CI: −2.9; 2.0). The relationship differed significantly only between baseline and 12-mo (β = 3.5, 95% CI: 0.3; 6.7). CONCLUSIONS: Findings suggest that mothers and toddlers exhibited similar dietary patterns, they are of low diet quality, and that diet quality decreased with maternal anxiety. Toddlerhood is often characterized by food neophobia and pickiness, which are common sources of maternal anxiety. Therefore, promoting anxiety-reducing strategies into maternal and toddler care and feeding behaviors guideline may be necessary. FUNDING SOURCES: National Institute of Health (NIH), Eunice Kennedy Shriver National Institute of Child Health & Human Development (NICHD). SUPPORTING TABLES, IMAGES AND/OR GRAPHS: